1999
DOI: 10.1002/(sici)1099-1085(199905)13:7<977::aid-hyp785>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Downstream change in river bank erosion rates in the Swale-Ouse system, northern England

Abstract: Abstract:Few studies have considered downstream changes in bank erosion rates and variability along single river systems. This paper reports some preliminary results of an intensive and direct ®eld monitoring exercise of bank erosion rates on 11 sites along 130 km of the 3315 km 2 Swale-Ouse river system in northern England over a 14 . 5 month period. Data were collected at active sites using grid networks of erosion pins read at c. 18±30 day intervals and bank-line resurveys. Erosion rates were relatively hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(80 citation statements)
references
References 32 publications
2
77
0
1
Order By: Relevance
“…Hooke (1979), Nanson and Hickin (1986), MacDonald (1991), and Lawler et al (1999) found that lateral migration rates increase with flow energy in meandering rivers. Bledsoe and Watson (2001) found that measures of stream power were significantly correlated with the degree of lateral stability in river channels measured by the transition to braiding.…”
Section: Lateral Movementssupporting
confidence: 68%
See 1 more Smart Citation
“…Hooke (1979), Nanson and Hickin (1986), MacDonald (1991), and Lawler et al (1999) found that lateral migration rates increase with flow energy in meandering rivers. Bledsoe and Watson (2001) found that measures of stream power were significantly correlated with the degree of lateral stability in river channels measured by the transition to braiding.…”
Section: Lateral Movementssupporting
confidence: 68%
“…Habitat restoration efforts often require a laterally mobile channel whereas engineering management often attempts to reduce risk to riverside structures and communities through a laterally stable channel. Lateral migration rates can vary both spatially and temporally within a single river reach (e.g., Hooke, 1980;Lawler et al, 1999). Anthropogenic impacts such as dam construction can affect migration rates as well (e.g., Xu, 1996Xu, , 1997Shields et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Subaerial erosion involves changes in soil moisture, which effectively weakens the streambank leading to the collapse of slabs of soil [15,17]. Hydraulic erosion, including sediment transport due to turbulent flows, may be more pronounced following subaerial erosion [16].…”
Section: Introductionmentioning
confidence: 99%
“…Given the apparent sensitivity of phytoplankton growth to shading, the relatively higher concentrations in the Swale of light-attenuating suspended sediments (SS) ( Table 1) may offer an explanation. The predominant source of the elevated levels in the Swale has been attributed to bank erosion (Lawler et al, 1999). Furthermore, the middle reaches of the Swale are more densely shaded by trees than those in the Ure.…”
Section: Biological Responsementioning
confidence: 99%